If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -2) + (-4x + 5) = -35 Reorder the terms: 4(-2 + 3x) + (-4x + 5) = -35 (-2 * 4 + 3x * 4) + (-4x + 5) = -35 (-8 + 12x) + (-4x + 5) = -35 Reorder the terms: -8 + 12x + (5 + -4x) = -35 Remove parenthesis around (5 + -4x) -8 + 12x + 5 + -4x = -35 Reorder the terms: -8 + 5 + 12x + -4x = -35 Combine like terms: -8 + 5 = -3 -3 + 12x + -4x = -35 Combine like terms: 12x + -4x = 8x -3 + 8x = -35 Solving -3 + 8x = -35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8x = -35 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = -35 + 3 8x = -35 + 3 Combine like terms: -35 + 3 = -32 8x = -32 Divide each side by '8'. x = -4 Simplifying x = -4
| (3t-15)=(2t-10) | | Z=5x+5y | | e^5x+6=.62 | | 61-w=170 | | F(x)=x-2/x^2-9 | | 74-(3x+11)=3(x+7)+x | | 16-18+19-(14-22-(31-41))= | | 3w=6n+3 | | 3x2/3-16=59 | | (1-u)(5u+7)=0 | | 4(x+3)+8=4x+8 | | (7x+5y)dx+(5x-8y^3)dy=0 | | 4(3x+6)-7=11(x-9) | | 2a+b=29 | | x2/3=27 | | 6x^2-22x=8 | | -4=g^2-4g | | 8x+5y=245 | | x2/5=9 | | 7(1-q)=-3(5+3a) | | Ln(7x+7)=1 | | x1/3=2 | | 2x+8=6x+44 | | 7x-(7-4x)= | | 4(x+3)=5(x+2) | | 3-8x+4x^2=0 | | 14x^4-7x^2=3 | | 7v^2+v-6=0 | | r=g2-g1/l | | 10x+5=110 | | 3z+9z-5,8=3,8 | | 28+x=108-x |